2019
DOI: 10.11606/s1518-8787.2019053001054
|View full text |Cite
|
Sign up to set email alerts
|

Potential years of life lost due to oropharyngeal cancer in Brazil: 1979 to 2013

Abstract: OBJECTIVE: To estimate the years of life lost by the Brazilian population due to mouth and pharynx cancer from 1979 to 2013, and analyze the temporal trends in the studied period, according to the country’s region, sex and anatomical site. METHODS: The death records were obtained from the Mortality Information System and the data referring to the population, from the censuses of the Brazilian Institute of Geography and Statistics of 1980, 1991, 2000, 2010, and from intercensal estimates for the other years. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 17 publications
6
9
0
Order By: Relevance
“…Perea et al (2018) estimated 1,589,501 YPLLs due to deaths from oral and pharyngeal cancer from 1979 to 2013, in Brazil. The YPLLs due to COVID-19 corresponded to 80.6% of the YPLLs for these types of cancer during this 35-year historical period [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perea et al (2018) estimated 1,589,501 YPLLs due to deaths from oral and pharyngeal cancer from 1979 to 2013, in Brazil. The YPLLs due to COVID-19 corresponded to 80.6% of the YPLLs for these types of cancer during this 35-year historical period [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed with data from the 2010 decade had already observed reductions in the proportion of mortality rates between Brazilian men and women. 9,12,15 Cunha et al 15 found that the mortality rate from oral and oropharyngeal cancer increased from 1.21/100,000 inhabitants in 2000 to 1.48/100,000 inhabitants in 2013 for women, representing a significant increase that was not observed for men. Another study reported that a male-female ratio of 3.7:1 was observed for oral cancer mortality rates in 2013, which represented a reduction of 1.5% compared to the beginning of the time series in 2002.…”
Section: North Northeastmentioning
confidence: 99%
“…[5][6][7] In Brazil, despite nearly a century of fighting cancer, with oncological assistance programs and public policies based on prevention campaigns, the incidence of oral cancer is still high for both sexes in various regions of the country. 8,9 A recent study observed an average Brazilian mortality rate from oral and oropharyngeal cancer of 4.5/100,000 inhabitants for men and of 0.9/100,000 inhabitants for women, considering a temporal analysis from 1983 to 2017. 10 In Brazil, men have historically concentrated higher rates of incidence and mortality from oral and oropharyngeal cancer than women.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations